2006
DOI: 10.1183/09031936.06.00025506
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of airway smooth muscle RhoA/ROCK activities by cholinergic and bronchodilator stimuli

Abstract: The current study set out to compare the temporal relationships of Rho activity, Rho kinase (ROCK) activity and tone following cholinergic stimulation in the presence and absence of three different bronchodilators.Bovine trachea challenged with a half-maximally effective concentration of carbachol (CCh) was flash-frozen at different times, then assayed for Rho (rhotekin pull-down assay) and ROCK (Western blot; radiometric assay) activities.Rho was activated within 30 s, followed by ROCK (peak at 2 min); both r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
33
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…RhoA-mediated ROCK activation and regulation of MLC phosphatase have been demonstrated during the cholinergic activation of airway smooth muscles (24,34,50). We found that stimulation with ACh increased the phosphorylation of the myosin regulatory subunit (MYPT1) of MLC phosphatase at Thr850, and that ACh-induced MYPT1 phosphorylation was completely inhibited by the inactivation of RhoA.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…RhoA-mediated ROCK activation and regulation of MLC phosphatase have been demonstrated during the cholinergic activation of airway smooth muscles (24,34,50). We found that stimulation with ACh increased the phosphorylation of the myosin regulatory subunit (MYPT1) of MLC phosphatase at Thr850, and that ACh-induced MYPT1 phosphorylation was completely inhibited by the inactivation of RhoA.…”
Section: Discussionmentioning
confidence: 74%
“…We conclude that the RhoA-mediated regulation of ACh-induced contractile tension in ASM results from its role in mediating actin polymerization rather than from effects on MLC phosphatase or MLC phosphorylation. cytoskeleton; calcium sensitization; myosin light chain phosphorylation; myosin light chain phosphatase; myosin phosphatase; calyculin A; myosin light chain kinase THE EFFECTS OF THE SMALL GTPase RhoA in regulating the Ca 2ϩ sensitivity of smooth muscle contraction are well documented and have been described for many smooth muscle tissue types, including airway smooth muscle (10,14,15,19,21,26,34,35,45,47,53). The effects of RhoA on the Ca 2ϩ sensitivity of contraction have been ascribed to its role in regulating the catalytic activity of smooth muscle myosin light chain (MLC) phosphatase (23,33,47,53).…”
mentioning
confidence: 99%
“…Whilst they show that activation of RhoA, Rho kinase, MYPT1 phosphorylation and constriction were sequential as expected, with RhoA activation reaching a peak after ,1 min but tension still increasing at 5 min [8], after 5 min there was a disassociation of tension from RhoA/Rho kinase activity, as tension continued to increase over the next 10 min whilst RhoA and Rho kinase activity declined by ,.50%. This differs from VSM, where agonist-induced RhoA activation is reported to be sustained and parallels force [9].…”
mentioning
confidence: 60%
“…Therefore, the study by LIU et al [8] in the current issue of the European Respiratory Journal is a welcome addition to the literature, although it raises some intriguing questions.…”
mentioning
confidence: 97%
See 1 more Smart Citation